O consumo de marcas premium pelo público jovem feminino de classe média - (:unkn) unknown (Universidade Federal do Pampa, 2011)
The increasing modern societies’ sophistication has led the consumers to seek not only for the satisfaction of basic needs, but also products and services with symbolic and emotional means. Furthermore, the increase in the standard of living in many places has collaborated, in the last decades, for a significant market grown in consumption of brand products considered premium, taking in consideration their symbolic value. This way, it is important to investigate and analyze which factors have influenced the costumers to buy these products (SOLOMON,2005). The research aims to study the reasons for buying premium brand products by the middle-class, young women consumers. Thus, the references in this final study discuses as the main themes: consumer behavior, social class, premium brands and the consumption influences. Concerning this, it is an exploratory and descriptive study, the data has been collected through a focus group with middle class, young women previously defined. It has been found that the factors which shows more motivate the consumption of the premium brand products are quality, distinction and also the exclusivity, and that they should have been taken in consideration by the brands in order to loyalty the consumers.
Consumption of premium brands by middle-class female youth
Keywords: Marketing; Comportamento do Consumidor; Marcas Premium; Influências no Consumo; Consumo Feminino; Exclusividade; Distinção; Exclusivity and distinction; Consumer behavior; Premium brands; Consumption influences; Female consumption; CNPQ::CIENCIAS SOCIAIS APLICADAS